Development of Volleyball Underhand Passing Skill Test Instrument for High School Students - Kristiwi Kusumaning Novadona; Mashuri Eko Winarno (STKIP Paasundan Press, 2025)
From observations conducted on students and teachers, researchers identified an issue in the volleyball skill assessment rubric, particularly in the basic technique of underhand passing. The study aimed to develop a valid, reliable, and objective volleyball skill testing instrument for 28 11th grade students at SMAN 1 Srengat Blitar. The development process used the research model proposed by Kirkendall, which initially consisted of 11 steps, but was simplified into 6 steps: determining test objectives, selecting and compiling tests, preparing equipment, compiling tests, conducting test trials, determining validity, reliability, objectivity, and practicality. From the test trial results, it was found that the validity for underhand passing resulted in a validity of 0.86 (excellent), reliability of 0.89 (good), and objectivity of 0.90 (acceptable). This indicates that the skill test instrument is feasible and practical to use. The conclusion of the study is that the testing instrument for implementing underhand passing in volleyball has met the standards related to validity, reliability, objectivity, and practicality. To expand the reach of this product, the researchers recommend re-evaluating it and adapting it to the target audience, both in terms of content and presentation. This will make the development of a volleyball skills test instrument for eleventh-grade students at SMAN 1 Srengat Blitar more engaging and useful